Ice particle morphology and microphysical properties of cirrus clouds inferred from combined CALIOP‐IIR measurements. Issue 8 (19th April 2017) - Saito, Masanori; Iwabuchi, Hironobu; Yang, Ping; Tang, Guanglin; King, Michael D.; Sekiguchi, Miho
Abstract: Ice particle morphology and microphysical properties of cirrus clouds are essential for assessing radiative forcing associated with these clouds. We develop an optimal estimation‐based algorithm to infer cirrus cloud optical thickness (COT), cloud effective radius (CER), plate fraction including quasi‐horizontally oriented plates (HOPs), and the degree of surface roughness from the Cloud Aerosol Lidar with Orthogonal Polarization (CALIOP) and the Infrared Imaging Radiometer (IIR) on the Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) platform. A simple but realistic ice particle model is used, and the relevant bulk optical properties are computed using state‐of‐the‐art light‐scattering computational capabilities. Rigorous estimation of uncertainties related to surface properties, atmospheric gases, and cloud heterogeneity is performed. The results based on the present method show that COTs are quite consistent with other satellite products and CERs essentially agree with the other counterparts. A 1 month global analysis for April 2007, in which CALIPSO off‐nadir angle is 0.3°, shows that the HOP has significant temperature‐dependence and is critical to the lidar ratio when cloud temperature is warmer than −40°C. The lidar ratio is calculated from the bulk optical properties based on the inferred parameters, showing robust temperature dependence. The median lidar ratio of cirrus clouds is 27–31 sr over the globe. Key Points: Cirrus cloud particle morphology is inferred from satellite measurements with an optimal estimation The retrievals are validated with multiple satellite products on a pixel‐by‐pixel basis The lidar ratio is affected by horizontally oriented particles where the temperature is greater than −40°C